EVALUASI PERLAKUAN AKUNTANSI PENDAPATAN PREMI DAN BEBAN KLAIM ASURANSI KESEHATAN (STUDI KASUS PSAK NO. 28 PADA PT. PRUDENTIAL LIFE ASSURANCE TAHUN 2012 - 2013) - Putra, Rizki Eka (MEASUREMENT : Jurnal Program Studi Akuntansi, 2014)
The purpose of this research is to determine whether the accounting treatment of premium income and health insurance claims expense in accordance with Statement of Financial Accounting Standards (SFAS) No. 28 about insurance at PT. Prudential Life Assurance. By the way do Recognition, Registration and Disclosure in premium income and the burden of claims contained in the Company and the treatment Statement of Financial Accounting Standards (SFAS).Â The results of this study it was concluded that In Premium income in PT. Prudential Life Assurance accounting treatment of the recognition, recording and disclosure in accordance with Statement of Financial Accounting Standards (SFAS) 28. And at the expense claim in PT. Prudential Life Assurance accounting treatment on the recognition and disclosure in accordance with Statement of Financial Akuntasni Standards (SFAS) 28 While the listing does not claim expenses in accordance with Statement of Financial Akuntasni Standards (SFAS) 28.Â Keywords: Premium Income and Expense Claims